2014
DOI: 10.1097/aog.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Vein Thrombophlebitis Related to Large Uterine Myoma

Abstract: Ovarian vein thrombophlebitis should be considered in patients with abdominal pain, fever, and evidence of venous stasis, even if they are lacking typical risk factors of pregnancy or surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…OVT occurs in the setting of Virchow's triad, which includes venous stasis, coagulation cascade activation and venous damage leading to hypercoagulable state, hence more common in pregnancy, postpartum, malignancy, and thrombophilias [2][3][4]. Less frequently, pelvic infections can also cause OVT and should be considered among differentials [1].…”
Section: Discussionmentioning
confidence: 99%
“…OVT occurs in the setting of Virchow's triad, which includes venous stasis, coagulation cascade activation and venous damage leading to hypercoagulable state, hence more common in pregnancy, postpartum, malignancy, and thrombophilias [2][3][4]. Less frequently, pelvic infections can also cause OVT and should be considered among differentials [1].…”
Section: Discussionmentioning
confidence: 99%
“…Результаты исследований, посвященных изучению роли ингибитора активатора плазминогена (ИАП) в общем ге-Gynecology мостазиологическом неблагополучии у больных СПКЯ, показывают, что уровень и активность ИАП-1 значительно выше у пациенток с данным синдромом по сравнению со здоровыми женщинами сходного возраста [20,21]. Несколько работ с малым количеством наблюдений [22,23] касались уровня антиплазмина и активируемого тромбином ингибитора фибринолиза (АТИФ). При этом статистической разницы в уровне антиплазмина выявлено не было.…”
Section: патогенетические аспекты спкя и мсunclassified
“…However, several studies have reported the role of thrombosis in myoma tumors, which support the development of coagulation in myoma cases; there is no published research on the role of coagulation factors in myoma based on our knowledge [12,18].…”
Section: Introductionmentioning
confidence: 99%